Simultaneous removal of nitrogen and pharmaceutical and personal care products from the effluent of waste water treatment plants using aerated solid-phase denitrification system - Sun, Haimeng; Ting Wang; Yang, Zhongchen; Yu, Cecilia; Wu, Weizhong (BIORESOURCE TECHNOLOGY, 2019)
Nowadays, waste water treatment plants (WWTPs) are regarded as the pollution sources of nitrogen and pharmaceutical and personal care products (PPCPs). In the present study, the simultaneous removal of nitrogen and typical PPCPs, ibuprofen and triclosan, was evaluated in a poly-3-hydroxybutyrate-co-3- hydroxyvalerate (PHBV) based solid-phase denitrification (SPD) system. Results after 602 days showed that simultaneous nitrification and denitrification (SND) process occurred with average 83.85 +/- 13.09% NH4 (+) -N and 93.88 +/- 10.19% NO3- -N removals in the SPD system. Interestingly, the system achieved average 79.69 +/- 6.35% and 65.96 +/- 7.62% removals of ibuprofen and triclosan, respectively, under stable influent conditions of 50 mu g L-1. Cometabolic activities of heterotrophic denitrifying bacteria and ammonia oxidizing bacteria (AOB) probably played a role in the biodegradation of the two PPCPs. Illumina MiSeq sequencing results revealed that microbial composition enhanced the simultaneous removal of nitrogen and PPCPs in the SPD system.